Methodological recommendations for lectures and seminars in the discipline "Family Law" for students of the Bachelor's degree program of specialty 081 "Law" - Piddubnyi, Oleksiy; Starchenko, O.; Adamovych, O. (My University, 2023)
The purpose of the discipline "Family Law" is to form a system of knowledge about the concept, subject and method of family law, its sources, functions and principles, basic institutions, features of legal regulation of family legal relations and general patterns and characteristics of the emergence, functioning and changes in family legislation in Ukraine.
Approved by the Academic Council of the Law Faculty.
Keywords: Family Law; Law